Finding Meaning in Education - Tunku Ahmad, Tunku Badariah (IIUM Press, 2018)
As educators, we often ask ourselves, “Is there meaning in what we teach? If there is, what is that meaning? And do students see the meaning we see? The meaning we want them to see?” Perhaps for many of us teachers and educators, we struggle to build meaning into our teaching, to give context to content, to make learning relevant, and to make students’ coming to class, not in vain. When students “see” the meaning of classroom content in daily life—how it might help them in their various endeavors—that is when we can consider our teaching successful. That perhaps, education has taken place. Finding ways and means of building meaning into teaching is a lifelong struggle for many educators. Some find it in the methods they use to deliver content; some may employ technology tools. Others may reach out to parents and the wider community to help forge this meaning.